Polymerization-Induced Self-Assembly: Ethanolic RAFT Dispersion Polymerization of 2 Phenylethyl Methacrylate - Pei, Y.; Lowe, Andrew (R S C Publications, 2014)
Reversible addition-fragmentation chain transfer (RAFT) radical dispersion polymerization (RAFTDP) has been employed to polymerize 2-phenylethyl methacrylate (PEMA) using poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) macromolecular chain transfer agents (macro-CTAs) of varying average degree of polymerization (Xn). RAFTDP of PEMA in ethanol at 70 C with PDMAEMA macro-CTAs yields well-defined AB diblock copolymers that self-assemble in solution during polymerization leading to the formation of well-defined diblock copolymer nanostructures. A full morphology transition (from spheres to worms to vesicles) is observed with these formulations that is sensitive to (i) the target X n of the solvophobic polyPEMA block, (ii) the total solids content at which the PEMA block copolymerization is performed and (iii) the target Xn of PDMAEMA as a macro-CTA. Finally, we demonstrate the ability to convert the PDMAEMA–PPEMA based nanoparticles to the corresponding sulfopropylbetaine analogues by the facile reaction of the DMAEMA residues with 1,3-propanesultone.